2003
DOI: 10.1519/1533-4287(2003)017<0484:eossot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Static Stretching of the Biceps Brachii on Torque, Electromyography, and Mechanomyography During Concentric Isokinetic Muscle Actions

Abstract: The purpose of this study was to determine the effect of an acute static stretching bout of the biceps brachii on torque, electromyography (EMG), and mechanomyography (MMG) during concentric isokinetic muscle actions. Eighteen (men, n ϭ 10; women, n ϭ 8) adult subjects (M Ϯ SD age ϭ 22.7 Ϯ 2.8 years; weight ϭ 78.0 Ϯ 17.0 kg; height ϭ 177.9 Ϯ 11.0 cm) performed maximal isokinetic (30 and 270Њ·s Ϫ1 ) forearm flexion strength testing on 2 occasions while EMG and MMG were recorded. Subjects were randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
99
4
17

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 95 publications
(138 citation statements)
references
References 11 publications
18
99
4
17
Order By: Relevance
“…1a) as a result of the static stretching. These findings were consistent with previous studies (Avela et al 1999;Behm et al 2001;Cramer et al 2004;Evetovich et al 2003;Fowles et al 2000;Kokkonen et al 1998;Sands 2001, 2003;Nelson et al 2001a, b;Young and Elliott 2001) that have reported decreases in the force producing capabilities of a muscle following a bout of static stretching. Nelson et al (2001b), however, reported stretching-induced decreases in isokinetic PT of the leg extensors at 60°AEs À1 and 90°AEs À1 (7.2% and 4.5% decreases, respectively), but no changes at 150°AEs À1 , 210°AEs À1 , or 270°AEs À1 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…1a) as a result of the static stretching. These findings were consistent with previous studies (Avela et al 1999;Behm et al 2001;Cramer et al 2004;Evetovich et al 2003;Fowles et al 2000;Kokkonen et al 1998;Sands 2001, 2003;Nelson et al 2001a, b;Young and Elliott 2001) that have reported decreases in the force producing capabilities of a muscle following a bout of static stretching. Nelson et al (2001b), however, reported stretching-induced decreases in isokinetic PT of the leg extensors at 60°AEs À1 and 90°AEs À1 (7.2% and 4.5% decreases, respectively), but no changes at 150°AEs À1 , 210°AEs À1 , or 270°AEs À1 .…”
Section: Discussionsupporting
confidence: 92%
“…It was concluded that the decreases in PT after stretching were velocity-specific and occurred primarily under the high torque production conditions associated with the slower velocities (60°AEs À1 and 90°AEs À1 ), but not the lower torque production conditions at the faster velocities (150°AEs À1 , 210°AEs À1 , and 270°AEs À1 ) (Nelson et al 2001b). The present findings, as well as those of previous studies (Cramer et al 2004;Evetovich et al 2003), however, indicated decreases in PT at both slow (30°AEs À1 and 60°AEs À1 ) and fast (240°AEs À1 and 270°AEs À1 ) velocities (for the stretched limb) and suggested that the stretching-induced decreases in PT may not be as velocity-specific (for the stretched limb) as suggested by Nelson et al (2001b). According to Fowles et al (2000), however, the magnitude of the inhibitory effect of stretching may be influenced by the magnitude of the stretch.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations